Meaning the Qualety of Life in Jabalpur city : An Integrated Approach - Tiwari, Rambooshan; Singh, Jagadish (National Geographical Journal of India, 2022)
The large concentrations of population in a small area on the one hand and haphazard and unorganized development on the other hand have created many problems for the good life and healthy living in a city. People living over a small area not only struggle for space in the city but also for easy availability of and access to infrastructural facilities, public amenities and quality environment. As a result, differences exist in quality of life at various levels. It is, therefore, necessary to have an understanding of its residents, how they live. The notion of quality of life may vary across the regions as well as scientific disciplines. Social scientists including geographers adopted objectives and subjective approaches to measure quality of life. The quality of life may be assessed through objective indicators such as availability of amenities and basic facilities at household level. It may also be judged on the basis of subjective indicators based on feelings and/ or experiences of satisfaction or dissatisfaction of individuals or groups with living conditions. Following both approaches, this study attempts to measure quality of life in Jabalpur - a million+ city of India focusing on four aspects viz. basic amenities, living conditions, social goods and environment. Based on sixty eight variables, a composite index is calculated to measure quality of life. In accordance, each of 480 survey households was classified into three categories of quality of life namely low, moderate and high. Further, spatial variations in the quality of life are examined by background characteristics of the residents. The results of this study may be useful for urban planners and decision makers to prioritize their efforts in ensuring good life and healthy environment for work and living.